Pharmacological decrease of liver stiffness is pressure-related and predicts long-term clinical outcome - Piecha, Felix; Poth, Tanja; Seitz, Helmut K.; Mueller, Sebastian (American journal of physiology. Gastrointestinal and liver physiology, 2018)
Liver stiffness (LS) as measured by transient elastography is increasingly used to noninvasively assess liver fibrosis. However, LS is efficiently modulated by confounders like arterial and portal pressure (PP). We here study the effect of acute hemodynamic changes on LS (measured by µFibroscan) in a rodent model of cirrhosis in response to pharmacological modulation of PP by losartan, nitric oxide donors, and propranolol.